Oral cavity melanoma in dogs: epidemiological, clinical and pathological characteristics (Research, Society and Development, 2022)
Oral cavity melanoma is a malignant neoplasm that originates in melanocytes. The prognosis is most often unfavorable, as it develops in an aggressive, invasive and metastatic way, which reflects in a short survival time after treatment. Considering this, the main purpose of this literature review was to establish the epidemiological, clinical and pathological aspects of oral cavity melanoma in dogs, aiming to gather information that may be essential for diagnosis, treatment and prognosis. The methodology was a qualitative bibliographic review through articles and works published during the period from 2017 to 2022 in the Scielo, Pubvet, Google Scholar databases, specialized veterinary scientific journals, in addition to consultations in small animal surgery books. Improved prognosis in cases of oral cavity melanoma depends on factors such as tumor location, size, and whether there is regional or distant metastasis. In addition, early diagnosis of the neoplasm will allow the treatment of tumors in early and non-metastatic stages, facilitating surgical removal and the effect of adjuvant therapies for treatment, in addition to preventing recurrences. For an early diagnosis to be possible, tutors must be instructed to examine their dogs' oral cavity regularly in search of lesions or nodules, and in this way, when melanoma is detected and diagnosed, the best treatment must be started quickly, allowing greater chances of survival or increased survival time of the animal.